Flux-quench induced dynamical quantum phase transitions in an extended XY spin-chain - Nie, Wen-Hui; Zhang, Mei-Yu; Wang, Lin-Cheng (Physica A, 2024)
Dynamical quantum phase transitions (DQPTs) induced by flux-quench in an extended transversed XY spin-chain have been investigated in this paper. We discussed the conditions for the appearance of DQPTs, and the different regions of the flux quench restricted by strength of transverse field were given. The Loschmidt echo, rate function, geometric phase, as well as dynamical topological order parameter (DTOP) have been calculated, which consistently verified the emergence of DQPTs.